The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22041900
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships and Adaptation in Deep-Sea Mussels: Insights from Mitochondrial Genomes

Abstract: Mitochondrial genomes (mitogenomes) are an excellent source of information for phylogenetic and evolutionary studies, but their application in marine invertebrates is limited. In the present study, we utilized mitogenomes to elucidate the phylogeny and environmental adaptation in deep-sea mussels (Mytilidae: Bathymodiolinae). We sequenced and assembled seven bathymodioline mitogenomes. A phylogenetic analysis integrating the seven newly assembled and six previously reported bathymodioline mitogenomes revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
8
16
1
Order By: Relevance
“…1B and Fig. S3), which is consistent with the result of our previous estimation based on the entire mitogenomes [28]. Gene family analyses revealed the expansion of 17 pfam domains in B. marisindicus (Fig.…”
Section: Characteristics Of the Hologenomesupporting
confidence: 91%
See 1 more Smart Citation
“…1B and Fig. S3), which is consistent with the result of our previous estimation based on the entire mitogenomes [28]. Gene family analyses revealed the expansion of 17 pfam domains in B. marisindicus (Fig.…”
Section: Characteristics Of the Hologenomesupporting
confidence: 91%
“…Although often presumed to lack function, pseudogenes may play important biological roles [30], particularly in the regulation of symbiosis [8]. In the present study, 6,026 pseudogenes were identified in the B. marisindicus genome, significantly lower than those reported in A. marissinica (10,211), although the latter has a somewhat higher number of PCGs (28,949) [8]. This larger number of pseudogenes in A. marissinica may be related to the expansion of TEs [8].…”
Section: Characteristics Of the Hologenomecontrasting
confidence: 48%
“…Apparent tRNA gene duplications were observed in three of eight putative species examined, involving trnS1, H, D, Y, Q, and M , with putative copy numbers ranging from 2 to 5 per genome. Similarly multiple tRNA gene copies have been reported on other bivalve mitochondrial genomes, for example, in bathymodiolin mussels ( Zhang et al 2021 ). Moreover, in one putative species, represented by xylophagaid specimens E23 and E81, there is an apparent tandem duplication of the rrnS and trnM genes.…”
Section: Resultssupporting
confidence: 70%
“…no Species and references Acc. no Arcuatula senhousia F 41 GU001953 Modiolus nipponicus 94 MK721547 Arcuatula senhousia M 41 GU001954 Modiolus philippinarum 95 KY705073 Bathymodiolus aduloides 96 MT916741 Mytella strigata MT991018 Bathymodiolus azoricus 96 MT916742 Mytilaster solisianus 71 KM655841 Bathymodiolus brooksi 96 MT916743 Mytilisepta keenae 94 MK721542 Bathymodiolus japonicus 97 AP014560 Mytilisepta virgata 94 MK721548 Bathymodiolus marisindicus 96 MT916745 Mytilus californianus F 42 GQ527172 Bathymodiolus manusensis KY270856 Mytilus californianus M 42 GQ527173 Bathymodiolus securiformis NC_039552 Mytilus chilensis 98 KT966847 Bathymodiolus septemdierum 97 AP014562 Mytilus unguiculatus 99 KJ577549 ...…”
Section: Methodsmentioning
confidence: 99%